2007
DOI: 10.1016/j.yjmcc.2007.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Rapid attenuation of circadian clock gene oscillations in the rat heart following ischemia–reperfusion

Abstract: The intracellular circadian clock consists of a series of transcriptional modulators that together allow the cell to perceive the time of day. Circadian clocks have been identified within various components of the cardiovascular system (e.g. cardiomyocytes, vascular smooth muscle cells), and possess the potential to regulate numerous aspects of cardiovascular physiology and pathophysiology. The present study tested the hypothesis that ischemia/reperfusion (I/R; 30 minute occlusion of the rat left main coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 33 publications
1
40
0
1
Order By: Relevance
“…As such, both intracellular and extracellular factors should be considered as important mediators of circadian rhythms in cardiovascular function. We speculate that impairment of this molecular mechanism may contribute toward myocardial contractile dysfunction associated with pressure overload, diabetes mellitus, myocardial infarction, and/or shift work (conditions in which the circadian clock within the heart is known to be altered) (9,18,43,45,46). Future studies should focus on addressing this important hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…As such, both intracellular and extracellular factors should be considered as important mediators of circadian rhythms in cardiovascular function. We speculate that impairment of this molecular mechanism may contribute toward myocardial contractile dysfunction associated with pressure overload, diabetes mellitus, myocardial infarction, and/or shift work (conditions in which the circadian clock within the heart is known to be altered) (9,18,43,45,46). Future studies should focus on addressing this important hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…Obesity, diabetes mellitus, hypertension, simulated shift work, aging, and ischemia/reperfusion have all been shown to influence this molecular mechanism. 12,[22][23][24][25][26][27] Coupled with the findings by Durgan et al, 21 the possibility arises that alterations in the clock mechanism during disease states contribute to greater tissue damage and contractile dysfunction following myocardial infarction. It remains to be seen if the human myocardium displays a similar response to the circadian clock.…”
mentioning
confidence: 90%
“…This attenuation was not observed with hypoxia induced by a hypobaric chamber, suggesting that the clock machinery is involved in the response to ischemia/reperfusion, independent of hypoxia. 99 Durgan et al showed that wild-type mouse hearts subjected to ischemia/reperfusion at the sleep-to-wake transition (ZT12) had a 3.5-fold increase in infarct size compared with hearts subjected to ischemia/ reperfusion at the wake-to-sleep transition (ZT0) and this variation was abolished in CCM mice. This study provides the first evidence that there is a time-of-day-dependent susceptibility to ischemia/reperfusion that is intrinsic to cardiomyocytes.…”
Section: Ischemia/reperfusionmentioning
confidence: 99%